To simplify the expression \(-0.3(-5a + 3b) + 9b - 0.9(7b + 8a)\), let's distribute the coefficients and combine like terms step by step.
-
Distribute \(-0.3\) to \(-5a + 3b\): \[ -0.3 \times -5a = 1.5a \] \[ -0.3 \times 3b = -0.9b \] So, \(-0.3(-5a + 3b) = 1.5a - 0.9b\).
-
Distribute \(-0.9\) to \(7b + 8a\): \[ -0.9 \times 7b = -6.3b \] \[ -0.9 \times 8a = -7.2a \] Thus, \(-0.9(7b + 8a) = -7.2a - 6.3b\).
-
Now, combine all the parts: \[ 1.5a - 0.9b + 9b - 7.2a - 6.3b \]
-
Combine like terms for \(a\): \[ 1.5a - 7.2a = -5.7a \]
-
Combine like terms for \(b\): \[ -0.9b + 9b - 6.3b = 1.8b \]
So, putting it all together, the simplified expression is: \[ -5.7a + 1.8b \]